Implementasi Model Pembelajaran Project Based Learning Pembuatan Lampu Taman Berbasis Energi Terbarukan untuk Meningkatkan Motivasi Belajar Murid SMA - Mufidah, Erna; Saputra, Bachtiar Adi (Lembaga Yasin AlSys, 2024)
This research aims to explore and apply the Project Based Learning (PjBL) Learning Model in the context of making renewable energy-based garden lights in high schools. The main focus of the research is to increase students' learning motivation through practical experience and real projects. Students are actively involved in every stage of making garden lights, from planning to implementation, while utilizing renewable energy sources. The research method used in this research was designed to achieve the objectives and answer the research questions asked. This research uses qualitative and quantitative approaches to gain a comprehensive understanding of the impact of implementing the Project Based Learning (PjBL) Learning Model on making renewable energy-based garden lights. The impact of implementing the Project Based Learning Model of Making Garden Lights Based on Renewable Energy to Increase High School Students' Learning Motivation is to foster students' critical thinking as seen from the responses and answers given by teachers during learning, increasing student activity as seen from students' activities during learning, can raise students' enthusiasm in learning accompanied by media displays of success or failure, media equipped with image and video displays, of the strategies carried out. This can be proven by the results of student learning evaluations above the KKM, student-centred activity design greatly increases student activity during the learning process so that students are motivated to learn. Overall, the implementation of the Project Based Learning (PjBL) learning model in making renewable energy-based garden lights has succeeded in increasing high school students' learning motivation. This success is reflected in students' positive responses to learning activities, where they expressed their excitement and satisfaction with the innovative learning approach and renewable energy-based projects. Positive impacts can also be seen from increasing students' critical thinking skills and activeness during the learning process.